Effects of foliar and root application of epsom salt on aquaponics beetroot (Beta vulgaris) production in confined condition - Akter, Shamima; Bablee, Alif Layla; Rana, KM Shakil; Nigar, Mahbuba; Nadia, Zubyda Mushtari; Salam, MA (Asian Journal of Medical and Biological Research, 2020)
The study was conducted to evaluate the impact of epsom salt, rich in magnesium and sulfur content beneficial to plant, on beetroot production in aquaponics system. Media based aquaponics systems (nine units) were employed for beetroot and tilapia culture where three treatments T1, T2 and T0 were applied with three replications (R1, R2, and R3) each. Epsom salt was applied in T1 as foliar spray in the form of 5% solution in each replication, whereas same amount of epsom salt (5 g) was directly applied on vegetable bed in T2 as root application. But in control (T0) no epsom salt was used. Beetroot saplings were planted in retrospect at a rate of two saplings per growbed (replication). After thirty days, plants grew enough to support the water clarification in aquaponics, ten tilapia fry were stocked per tank (90 L) in each replication. Fish were fed commercial floating feed containing 30% protein. Although the fish growth parameters in three treatments were statistically similar, the highest mean length gain, weight gain, specific growth rate and fish production were found 5.11±1.64 cm, 30.16±0.11 g, 0.39±0.01 %/day and 26.27±2.47 tons/ha/60 days respectively in T1 followed by T2 and T0. However, response of beetroots to different treatments was statistically different. The highest average leaf area (69.79 ± 0.48 cm2), length of root (31.03±0.43 cm), weight of root (21.17±1.92 g), and production of beetroot 8.67±1.54 tons/ha/90 days were found in T1 followed by T2 and T0. Harvesting time was also reduced in epsom salt based aquaponics system. The overall production of beetroot and tilapia was higher in T1 (foliar spray) than T2 (root application) and T0 (control). Thus, the study signifies the potentialities of epsom salt in aquaponics vegetable production. However, further research is needed to verify the dose response to epsom salt in aquaponics system. Asian J. Med. Biol. Res. March 2020, 6(1): 56-66